2022
DOI: 10.1039/d2py00040g
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous polymer synthesis delivered by multi-objective closed-loop optimisation

Abstract: Application of artificial intelligence and machine learning for polymer discovery offers an opportunity to meet the drastic need for the next generation high performing and sustainable polymer materials. Here, these...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…Both can be measured online in continuous flow, conversion via NMR spectroscopy, and average molecular weight via size exclusion chromatography (SEC). [8,17,24,34] Thanks to the miniaturization of NMR devices, coupling of flow reactors to benchtop models are made simple. [35] SEC is a little bit more tricky to couple online, as it relies on spaced injections into HPLC systems, and is hence non-continuous.…”
Section: Automated Polymer Screening Platformmentioning
confidence: 99%
“…Both can be measured online in continuous flow, conversion via NMR spectroscopy, and average molecular weight via size exclusion chromatography (SEC). [8,17,24,34] Thanks to the miniaturization of NMR devices, coupling of flow reactors to benchtop models are made simple. [35] SEC is a little bit more tricky to couple online, as it relies on spaced injections into HPLC systems, and is hence non-continuous.…”
Section: Automated Polymer Screening Platformmentioning
confidence: 99%
“…[26] This approach involves mathematical models with closed loops where the recorded information of an experiment influences the experimental conditions for the following ones. [41] The more extensively used algorithm for selfoptimisation is the Nelder-Mead Simplex Method, [42] but there are also examples of the use of others like a modified version known as Complex, [43] Mie, [4b] TSEMO [44] or SNOBFIT. [45] Figure 5 illustrates the general workflow for automated selfoptimising systems: Initial experimental conditions are set, the output of the reactor is recorded and according to the received signal new experimental conditions are chosen by the algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Further, their approach is particularly effective for solvents in which SEC analysis may be challenging. 91 Recently, Knox et al 92 demonstrated multiobjective optimization of RAFT by applying Thompson sampling efficient multiobjective optimization algorithm to resolve the trade-off between dispersity and monomer conversion without any human intervention. This study relied heavily on inline analysis to ensure that their algorithm could be deployed effectively in real-time even if batch processes enable automated synthesis of a large numbers of polymers, bottlenecks will arise from downstream operations such as NMR and SEC analysis, polyplex formation, physical characterization, and sample preparation for biological testing.…”
Section: Polymer Libraries Via Reversible-deactivation Radical Polyme...mentioning
confidence: 99%